If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 1) + -5x = x + 6 Reorder the terms: 6(1 + x) + -5x = x + 6 (1 * 6 + x * 6) + -5x = x + 6 (6 + 6x) + -5x = x + 6 Combine like terms: 6x + -5x = 1x 6 + 1x = x + 6 Reorder the terms: 6 + 1x = 6 + x Add '-6' to each side of the equation. 6 + -6 + 1x = 6 + -6 + x Combine like terms: 6 + -6 = 0 0 + 1x = 6 + -6 + x 1x = 6 + -6 + x Combine like terms: 6 + -6 = 0 1x = 0 + x 1x = x Solving 1x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 1x + -1x = x + -1x Combine like terms: 1x + -1x = 0 0 = x + -1x Combine like terms: x + -1x = 0 0 = 0 Simplifying 0 = 0 The solution to this equation could not be determined.
| 4x-8=6x-4 | | x^2+18x+35=0 | | x+y=a | | 2(3-2x)=1-4(x+3) | | x+3(12)=13 | | 30x-20x+8=15-5x | | y+3*-2=8 | | 49x*2+14x+1=0 | | 3x+1x=2x+4x | | y+3x-2=8 | | S(8)=62000(0.43046721) | | xy-y=0 | | 12+3y=13 | | -4x+5=-9x-20 | | 8+4x=(-10)+x | | 9(x-2)-5(-2x-5)=18(x-1)-6 | | -6-9-5*5= | | 5(5)+(6)=8 | | 7-7z=35 | | 12x=-3x | | 3x-5y=41-6x | | x^2-4x+11=0 | | s+1.5=0.8 | | 3(v-1)=6v-4 | | B(12+b)-7=2b+b(-4+b) | | 13x*2+5x+1=0 | | 2x+5-x=9-x+2 | | 1=0.4-0.6x-5 | | -8*-3+3*4= | | 2-3y=-8 | | -9(x-2)=-10x | | 31-17= |